(untitled) (Al-Academy, 2024)
The research aims to establish the roots of Saudi digital art. The objectives came within two paths, the first aims to trace the beginnings of the emergence of Saudi digital art, and the second to know the most important pioneers of Saudi digital art and know the most important Saudi digital artists. To achieve the research objectives, we relied on the historical approach through the chronology of events. One of the most important results that emerged is that Saudi digital art began in the early nineties of the twentieth century for commercial and journalistic purposes, and developed clearly at the beginning of the second millennium. One of the most important pioneers of this art is: Khaled Al-Amir. Ahmed Al-Qadi, Faisal Al-Mashari, and Fahd Al-Hujailan. One of the most important recommendations of this research is to increase interest in digital art by official cultural educational institutions.